Emotion work in interpreter-mediated consultations: A systematic literature review. Issue 1 (January 2020) - Theys, Laura; Krystallidou, Demi; Salaets, Heidi; Wermuth, Cornelia; Pype, Peter
Highlights: There is dearth of research on emotional communication in interpreted consultations. Participants in interpreted consultations can co-construct emotional communication. Interpreted consultations are marked by a decrease in emotional communication. Emotional communication should be enhanced to ensure the patient's quality of care. Abstract: Objective: To identify the ways in which physicians, patients and interpreters express emotions, react to emotional expressions and/or coordinate the emotional interaction in interpreter-mediated consultations (IMCs). Methods: We systematically searched four databases and screened 10 307 articles. The following inclusion criteria were applied: 1) participants are patients with limited proficiency in the host language, physicians and professional interpreters, 2) analysis of patient-physician-interpreter interaction, 3) focus on emotions, 4) in vivo spoken language interpretation, and 5) authentic primary data. Results: The results of 7 included studies suggest that physicians, patients and interpreters work together and verbally and paraverbally contribute to the co-construction of emotional communication (EC) in IMCs. However, a decrease in EC might still compromise the patient's quality of care in IMCs. Conclusion: There is a dearth of scientific evidence of EC as an interactional process between participants in IMCs. More research on under investigated modes of communication and emotions is needed to advance our understanding. For now, EC seems to be subject to the successful interaction between participants in IMCs. Practice implications: Evidence-based curricula of interprofessional education between physicians and interpreters on EC in IMCs could be beneficial to the effective co-construction of EC in IMCS.